Pseudomonas syringae isolated in lichens for the first time: Unveiling Peltigera genus as the exclusive host - Ramírez, Natalia; Sigurbjörnsdóttir, M. Auður; Monteil, Cecile; Berge, Odile; Heiðmarsson, Starri; Jackson, Robert W; Morris, Cindy E.; Vilhelmsson, Oddur (Environmental Microbiology, 2023)
International audience Pseudomonas syringae is a bacterial complex that is widespread through a range of environments, typically associated with plants where it can be pathogenic, but also found in non‐plant environments such as clouds, precipitation, and surface waters. Understanding its distribution within the environment, and the habitats it occupies, is important for examining its evolution and understanding behaviours. After a recent study found P . syringae living among a range of vascular plant species in Iceland, we questioned whether lichens could harbour P . syringae . Sixteen different species of lichens were sampled all over Iceland, but only one lichen genus, Peltigera , was found to consistently harbour P . syringae . Phylogenetic analyses of P. syringae from 10 sampling points where lichen, tracheophyte, and/or moss were simultaneously collected showed significant differences between sampling points, but not between different plants and lichens from the same point. Furthermore, while there were similarities in the P. syringae population in tracheophytes and Peltigera , the densities in Peltigera thalli were lower than in moss and tracheophyte samples. This discovery suggests P . syringae strains can localize and survive in organisms beyond higher plants, and thus reveals opportunities for studying their influence on P . syringae evolution.